The association between female reproductive performance and leukocyte telomere length in wild Soay sheep. Issue 23 (5th October 2021) - Ravindran, Sanjana; Froy, Hannah; Underwood, Sarah L.; Dorrens, Jennifer; Seeker, Luise A.; Watt, Kathryn; Wilbourn, Rachael V.; Pilkington, Jill G.; Harrington, Lea; Pemberton, Josephine M.; Nussey, Daniel H.
Abstract: Telomere length (TL), typically measured across a sample of blood cells, has emerged as an exciting potential marker of physiological state and of the costs of investment in growth and reproduction within evolutionary ecology. While there is mounting evidence from studies of wild vertebrates that short TL predicts raised subsequent mortality risk, the relationship between reproductive investment and TL is less clear cut, and previous studies report both negative and positive associations. In this study, we examined the relationship between TL and different aspects of maternal reproductive performance in a free‐living population of Soay sheep. We find evidence for shorter TL in females that bred, and thus paid any costs of gestation, compared to females that did not breed. However, we found no evidence for any association between TL and litter size. Furthermore, females that invested in gestation and lactation actually had longer TL than females who only invested in gestation because their offspring died shortly after birth. We used multivariate models to decompose these associations into among‐ and within‐individual effects, and discovered that within‐individual effects were driving both the negative association between TL and gestation, and the positive association between TL and lactation. This suggests that telomere dynamics may reflect recent physiologically costly investment or variation in physiological condition, depending on the aspect of reproduction being investigated. Our results highlight the physiological complexity of vertebrate reproduction, and the need to better understand how and why different aspects of physiological variation underpinning life histories impact blood cell TL.